2016
DOI: 10.1038/srep28442
|View full text |Cite
|
Sign up to set email alerts
|

Association between the ambient temperature and the occurrence of human Salmonella and Campylobacter infections

Abstract: Salmonella spp. and thermotolerant Campylobacter spp. are the most important causes of human bacterial diarrheal infections worldwide. These bacterial species are influenced by several factors like behaviour of the host, shedding, environment incl. directly or indirectly through ambient temperature, and the infections show seasonality. Therefore, the aim of our study was to investigate the association between the occurrence of human campylobacteriosis and salmonellosis and the ambient temperature. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
(35 reference statements)
3
27
1
2
Order By: Relevance
“…The authors concluded that the product contamination rate did not vary with season but that the undercooking of meat during the summer months may have been responsible for the seasonal variability. Other studies in Germany, Netherlands, England and Wales, Switzerland, Spain, Czech Republic, Denmark, and Australia also indicated a relationship between outdoor temperature and Salmonella illness in humans (5255). Improper food handling and increased bacterial growth in warm weather were considered potential factors that could contribute to the increased caseload.…”
Section: Discussionmentioning
confidence: 89%
“…The authors concluded that the product contamination rate did not vary with season but that the undercooking of meat during the summer months may have been responsible for the seasonal variability. Other studies in Germany, Netherlands, England and Wales, Switzerland, Spain, Czech Republic, Denmark, and Australia also indicated a relationship between outdoor temperature and Salmonella illness in humans (5255). Improper food handling and increased bacterial growth in warm weather were considered potential factors that could contribute to the increased caseload.…”
Section: Discussionmentioning
confidence: 89%
“…Another reason for the increasing case numbers, especially in the summer months from June to September, could be the increased ambient temperature. Yun and colleagues [23] showed that the increase in ambient temperature is positively associated with the occurrence of Campylobacter. Although the incidences of salmonellosis decreased from 2001 to 2016 in Germany, in 2018, the number of infections was higher than in 2016 [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of reports on the seasonality of Campylobacter colonization of birds and also human illness (Chowdhury et al 2013;Friedrich et al 2016;Yun et al 2016). Therefore, it was not surprising that the initial model (Fig.…”
Section: Discussionmentioning
confidence: 99%